2015
DOI: 10.1158/1078-0432.ccr-14-2744
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing in Conjunction with Expression and Functional Analyses Reveals Activation of FGFR1 in Ewing Sarcoma

Abstract: PURPOSE: A low mutation rate seems to be a general feature of pediatric cancers, in particular in oncofusion gene-driven tumors. Genetically, Ewing sarcoma is defined by balanced chromosomal EWS/ETS translocations, which give rise to oncogenic chimeric proteins (EWS-ETS). Other contributing somatic mutations involved in disease development have only been observed at low frequency. EXPER-IMENTAL DESIGN: Tumor samples of 116 Ewing sarcoma patients were analyzed here. Whole-genome sequencing was performed on two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 45 publications
7
56
2
Order By: Relevance
“…Although several potential molecular targets have been identified in Ewing sarcoma, their clinical trials aimed at these targets have yet to show success (53). Through high-throughput screens using both siRNA and small-molecule inhibitor libraries, we confirmed a number of previously reported Ewing sarcoma actionable candidates such as ERBB4, EGFR, ROR1, KIT, and FGFRs (9,(30)(31)(32)(33)(34)(35)(36)(37). Most importantly, we identified SYK as an important progrowth kinase in Ewing sarcoma through unbiased integrative approaches.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although several potential molecular targets have been identified in Ewing sarcoma, their clinical trials aimed at these targets have yet to show success (53). Through high-throughput screens using both siRNA and small-molecule inhibitor libraries, we confirmed a number of previously reported Ewing sarcoma actionable candidates such as ERBB4, EGFR, ROR1, KIT, and FGFRs (9,(30)(31)(32)(33)(34)(35)(36)(37). Most importantly, we identified SYK as an important progrowth kinase in Ewing sarcoma through unbiased integrative approaches.…”
Section: Discussionsupporting
confidence: 70%
“…As shown in Fig. 1A, the top 20 genes ranked by median inhibition rate values (MV) included a number of known oncogenic kinases in Ewing sarcoma, such as ROR1, KIT, FGFR, PTK families (PTK-2 and 7), Src families (FGR and SRMS), ERBB4, and EGFR (9,(30)(31)(32)(33)(34)(35)(36)(37), which strongly supported the methodology and effectiveness of our high-throughput screen. Importantly, we identified novel targets including SYK and related proteins (SYK and ZAP70), BTK, ABL1, FLT4, and MATK.…”
Section: High-throughput Sirna and Small-molecule Inhibitor Library Ssupporting
confidence: 69%
“…[25][26][27][28] However, the addition of adjunctive, immune-activating therapies during first remission demonstrated the potential to reduce recurrence rates and exploit immunotherapy approaches for ES patients. 29 Balanced chromosomal EWS/ETS translocations that give rise to oncogenic chimeric proteins (EWS-ETS), the most common being EWS-FLI1 as a consequence of the t(11;22)(q24; q12) translocation, 30,31 are the characteristic driver event of ES tumorgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ATP1A1 is required for unconventional secretion of FGF 54 , BCL11B promotes FGF-signaling by transcriptional suppression of a negative feedback inhibitor 44,55 , and GLG1 (alias cysteine-rich FGF receptor) is known to regulate intracellular levels of FGF 56 . Several studies have shown that FGF promotes EWSR1-FLI1 expression 57 and growth of Ewing sarcoma cells in vitro and in vivo 46,55 , and that FGF-inhibitors could be used as a targeted treatment for Ewing sarcoma patients 58 . Although more work needs to be done to elucidate the precise role of ATP1A1, BCL11B, and GLG1 in FGF-signaling, it is tempting to speculate that they could serve as predictive biomarkers for the efficacy of FGF-inhibitors.…”
Section: Discussionmentioning
confidence: 99%